Highly mobile insectivorous swifts perform multiple intra‐tropical migrations to exploit an asynchronous African phenology. Issue 5 (5th December 2018) - Norevik, Gabriel; Boano, Giovanni; Hedenström, Anders; Lardelli, Roberto; Liechti, Felix; Åkesson, Susanne
Abstract : With timely allocated movement phases, mobile organisms can match their space‐use with the seasonality of the environment and thereby optimise their resource utilisation over time. Long‐distance avian migrants are known to move with the seasonal dynamics on an annual basis, but how individuals respond to seasonality within their tropical non‐breeding range has been less studied. Here we analyse the movement pattern of a highly mobile aerial insectivorous bird, the pallid swift Apus pallidus, and its association with the local habitat phenology during the non‐breeding period, using individual‐based light‐level geolocation. We extracted timing and location of 21 birds' residence periods, as well as characteristics of the intervening movements, such as distance and speed. We used time series of precipitation and vegetation data for each residence area to extract the timing of the local end of the rainy season and the onset of the dry season. The pallid swifts repeatedly upgraded their habitat by undertaking 2–5 intra‐tropical migrations correlated with the withdrawal of the rains and the onset of the local dry season. The birds arrived to the sites on average 12 days after rains ended and departed about two weeks after the onset of dry season suggesting that the birds closely tracked a spatiotemporal window presumably timed with optimal foraging conditions. Our results provide insights in the ways Palaearctic–African migrants respond to the asynchronous phenology within their sub‐Saharan non‐breeding range. We confirmed that pallid swifts actively respond to deteriorating conditions by repeated upgrades in habitat quality, which likely have substantial consequences for an individual's access to an essential, spatiotemporally ephemeral food resource. However, the pallid swifts did not surf an apparent resource wave per se as would be expected in a highly mobile species, indicating that also other factors, such as spatial patchiness of resources, may influence the movement decision.